Confraternities as an Interface Between Citizens and Convent Musical Ceremonial in Sixteenth-Century Barcelona - Mazuela-Anguita, Ascensión (Confraternitas)

(untitled) (Iter Press, 2020)
Confraternities offer an example of the porosity of the early modern urban cloister for musical reasons. Many sixteenth-century Barcelonan guild and devotional confraternities were housed in nunneries and used conventual spaces that were also filled by the sound of nuns singing in the celebration of specified feasts as part of their devotional practices. This article, based on case-studies of the Benedictine convents of Sant Pere de les Puel·les and Sant Antoni i Santa Clara and the Dominican nunneries of Montsió and Els Àngels, analyzes a variety of archival documents in order to assess the close connection between the inhabitants of Barcelona and conventual ceremonies involving music through membership in a confraternity, the desire of members to be buried in convents, and the funerary ceremonies and eschatological beliefs this implied.